Myelodysplastic syndrome versus idiopathic cytopenia of undetermined significance : the role of morphology in distinguishing between these entities - Santos, Talyta Ellen de Jesus dos (2013)
Myelodysplastic syndrome (MDS) is a Heterogeneous group of diseases characterized by ineffective and dysplastic hematopoiesis and pancytopenia in the peripheral blood(1). Minimal diagnostic criteria for MDS have been discussed by several working groups.